2000
DOI: 10.1007/s003840050238
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sphincter morphology on endoanal MRI and histopathological aspects of the external anal sphincter

Abstract: Atrophy of the external anal sphincter can be shown only on endoanal magnetic resonance imaging (MRI). Until now no study has compared the morphological endoanal MRI findings with histopathological aspects of the external anal sphincter. The aim of this study was to validate the MRI interpretation of the external anal sphincter using histology as a "gold standard." In this prospective study 25 consecutive unselected women (median age 48 years, range 27-72) with fecal incontinence due to obstetric trauma were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 16 publications
1
27
0
5
Order By: Relevance
“…13). Endoanal MRI has been demonstrated to be accurate in this evaluation, which has been validated both surgically and histologically [28,30,31,32]. In a study with histological confirmation, endoanal MRI has been demonstrated to be accurate in determining the presence, as well as the absence, of external sphincter atrophy (14 of 15, 93%) [32].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…13). Endoanal MRI has been demonstrated to be accurate in this evaluation, which has been validated both surgically and histologically [28,30,31,32]. In a study with histological confirmation, endoanal MRI has been demonstrated to be accurate in determining the presence, as well as the absence, of external sphincter atrophy (14 of 15, 93%) [32].…”
Section: Discussionmentioning
confidence: 97%
“…Endoanal MRI has been demonstrated to be accurate in this evaluation, which has been validated both surgically and histologically [28,30,31,32]. In a study with histological confirmation, endoanal MRI has been demonstrated to be accurate in determining the presence, as well as the absence, of external sphincter atrophy (14 of 15, 93%) [32]. In a comparative study of endosonography and endoanal MRI in 20 women with faecal incontinence due to obstetric trauma, external sphincter atrophy was not identified at endosonography, when it was present at endoanal MRI in eight women [31].…”
Section: Discussionmentioning
confidence: 98%
“…Zum einen hat man die Muskelmasse direkt im MR vermessen und zum anderen hat man sich bemüht, den prozentualen Anteil des Fettgewebes im Muskel zu bestimmen, da die Muskulatur und das Fettgewebe ein unterschiedlich intensives Signal im MR besitzen [18]. Zusätzlich haben die Korrelation von histopathologischen Untersuchungen und MR-Bildern bestätigt, dass die Erscheinungen tatsächlich auf einen verminderten Durchmesser der Muskelfasern und einen Fettgewebsersatz zurückzuführen sind [3]. mit dem Alter des Patienten in einen Zusammenhang zu bringen.…”
Section: Atrophie Des M Sphincter Externusunclassified
“…This type of imaging has re-established the importance of anterior sphincteroplasty in these patients [35,36]. The high-resolution imaging afforded by close field endoanal MRI has also provided quality images of these defects and the expected postoperative appearance following sphincter repair [37][38][39], giving the impression that the amount of EAS atrophy adversely correlates with functional post-surgical outcome [40]. For these views, the technique has been well described.…”
Section: Functional Pelvic Disordersmentioning
confidence: 99%